A Constituição Federal de 1988 e a integração regional : o desafio da harmonização tributária - Clementino, Marco Bruno Miranda (2007)
As an effect of the growing interdependence in international relations, regional integration was conceived to face globalization, with a remarkable influence in politics and law, since the first steps of the European experience. In Latin America, regional integration ideas have blossomed in the 60 s. Among its experiences, MERCOSUL is the one with the most advanced objectives. However, MERCOSUL has not managed to achieve the objectives planned nor moved forward the integration process. Differently of what happened in Europe, in MERCOSUL the common market projected is concluded. It faced many disappointments throughout its brief history. As it matters to law, those were caused by the absence of supranationality, a mechanism that would allow MERCOSUL s decisions to be directly binding in the States with no need of bureaucratic proceedings to incorporate them to national legal systems. Among Latin American States, Brazil is probably the most resistant to integration process, due to Federal Constitution 1988 rigidity and legal professionals conservadorism towards opening legal system to international law. In Brazil hermeneutical standards are always based on national sovereignty and international law is referred as less important. The problems become more visible relating to taxation, a subject that plays an enormous role in integration process for its economic impact, demanding the execution of tax harmonization policies compatible to the integration levels aspired. However, because of the large number of tax rules in the Federal Constitution, structural changes initiatives face difficulties in order to be implemented. Actually, after two Constitutional Reforms on taxation, Brazil has not yet succeeded on promoting the necessary adaptations to regional integration. The research has confirmed the hypothesis that supranationality has indispensably to be adopted if Brazil really desires to move forward the integration process. But it has also been demonstrated that there are hermeneutical paths suitable to the constitutional profile which allow the adoption of supranationality, through the revision of the sovereignty traditional concept